2015
DOI: 10.15850/amj.v2n3.522
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge and Perception on Autopsy in Jatinangor, West Java from August to October 2013

Abstract: Background: Autopsy rate had declined dramatically throughout the world for the past decades. This phenomenon has raised concerns of the medical world. Factors that contributed to this decline include lack of knowledge regarding autopsy among the people, religious reasons, unenthusiastic pathologists and others. This study was conducted to discover the community knowledge and perception of autopsy at Jatinangor, West Java. Methods: A descriptive study was conducted in Jatinangor during the period of August to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, there are still 1 in 3 people who have poor knowledge of attitudes and perceptions about the autopsy, which is consistent with previous studies. 12,14 This study showed that most people answered at least the importance of an autopsy in both clinical autopsy and medicolegal autopsy, and only ten people said that autopsy was not important. As many as 92% supported the practice of autopsy, and 78.8% agreed to perform an autopsy on their family or relatives.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, there are still 1 in 3 people who have poor knowledge of attitudes and perceptions about the autopsy, which is consistent with previous studies. 12,14 This study showed that most people answered at least the importance of an autopsy in both clinical autopsy and medicolegal autopsy, and only ten people said that autopsy was not important. As many as 92% supported the practice of autopsy, and 78.8% agreed to perform an autopsy on their family or relatives.…”
Section: Discussionmentioning
confidence: 85%
“…10 This rejection can be caused by several factors such as lack of knowledge and inadequate perception of the autopsy. 6,12 Wrong perceptions circulating in the community, such as organs or tissues are taken and sold, or medical students use their organs and remain for practice. Apart from that, other factors also affect humanitarian reasons, religious differences, and administrative costs, which cause the next of kin to refuse to perform an autopsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation